Protocol of anther and microspore culture in cassava (androgenesis) = Protocolo para el cultivo de anteras y microsporas (androgénesis) en yuca/mandioca - Perera, Prasanthi I.P.; Golemiec, Elzbieta; Dedicova, Beata; Wedzony, Maria; Heberle-Bors, Erwin; Ordoñez, Carlos; Ceballos, Hernán (International Center for Tropical Agriculture, 2018)
This 9-minute video describes the protocol used for the collection of male flowers in cassava for the production of doubled haploids through androgenesis (in vitro microspore or anther culture). Pre-treatments and different culture conditions used in the process to induce cell division in immature microspores are described. Progress inducing cell division and calli was made, but no plants could be regenerated. Este video de 9 minutos describe el protocolo usado en la colección de flores masculinas de yuca/mandioca para la producción de doble haploides a través de androgénesis (cultivo de microsporas o anteras). Se muestran algunos de los pre-tratamientos así como condiciones de cultivo in vitro para inducir división celular en las microsporas. Se describen los éxitos alcanzados induciendo división celular y producción de callos. No se pudo, sin embargo, regenerar plantas.